Reproducibility assessment of ultrasound-based aortic stiffness quantification and verification using Bi-axial tensile testing. (March 2020) - van Disseldorp, Emiel M.J.; van den Hoven, Marcel H.M.H.; van de Vosse, Frans N.; van Sambeek, Marc R.H.M.; Lopata, Richard G.P.
Abstract: Current guidelines for abdominal aortic aneurysm (AAA) repair are primarily based on the maximum diameter. Since these methods lack robustness in decision making, new image-based methods for mechanical characterization have been proposed. Recently, time-resolved 3D ultrasound (4D US) in combination with finite element analysis was shown to provide additional risk estimators such as patient-specific peak wall stresses and wall stiffness in a non-invasive way. The aim of this study is to: 1) assess the reproducibility of this US-based stiffness measurement in vitro and in vivo, and 2) verify this 4D US stiffness using the gold standard: bi-axial tensile testing of the excised aortic tissue. For the in vitro study, 4D US data were acquired in an idealized inflation experiment using porcine aortas. The full aortic geometry was segmented and tracked over the cardiac cycle, and afterwards finite element analysis was performed by calibrating the finite element model to the measured US displacements to find the global aortic wall stiffness. For verification purposes, the porcine tissue was subjected to bi-axial tensile testing. Secondly, four AAA patients were included and 4D US data were acquired before open aortic surgery was performed. Similar to the experimental approach, the 4D US data were analyzed using the iterative finite element approach. During surgery, aortic tissue was harvested and the resulting tissue specimens were analyzed using bi-axial tensile testing. Finally, reproducibility was quantified for both methods. A high reproducibility was observed for the wall stiffness measurements using 4D US, i.e., an ICC of 0.91 (95% CI: 0.78–0.98) for the porcine aortas and an ICC of 0.98 (95% CI: 0.84–1.00) for the AAA samples. Verification with bi-axial tensile testing revealed a good agreement for the inflation experiment and a moderate agreement for the AAA patients, partially caused by the diseased state and inhomogeneities of the tissue. The performance of aortic stiffness characterization using 4D US revealed overall a high reproducibility and a moderate agreement with ex vivo mechanical testing. Future research should include more patient samples, to statistically assess the accuracy of the current in vivo method, which is not trivial due to the low number of open surgical interventions.